Smagen af køn: En gastrofeministisk læsning af Ainslie Hogarths Motherthing - Tarbensen, Mau Lindow (Passage - Tidsskrift for litteratur og kritik, 2025)
The Taste of Gender: A Gastrofeminist Reading of Ainslie Hogarth’s Motherthing This paper demonstrates how taste and gender can be read together in literary analysis. I argue that the affective anchoring of taste in Motherthing (2022) expresses a gastrofeminist critique of traditional and late modern gender norms. This initial step toward a gastrofeminist literary criticism suggests a potential for examining the connections between taste and gender in ecocritical fiction, thereby elucidating the social mechanisms that shape our food cultures.